Correlation of cerebral blood flow velocity with haematocrit in neonates at risk of polycythaemia: a COHORT study - Madarkar, Babu S.; C., Chandan; Devaranavadagi, Ranganatha A. (International Journal of Contemporary Pediatrics, 2024)
Background: The incidence of polycythemia is 1.5-4% of all live births. To diagnose polycythemia, a venous hematocrit is necessary, and polycythaemia is linked to changes in cerebral blood flow. The primary objective is to compare cerebral blood flow velocity (CBFV) and resistance index (RI) between polycythemia and normocythemia groups. The secondary objective is to correlate the peak systolic velocity (PSV) of anterior and middle cerebral arteries (ACA and MCA) with hematocrit in neonates at risk for polycythemia. Methods: In a prospective observational study, babies with a gestational age of >35 weeks and a risk factor for polycythaemia were enrolled in the study. Free-flowing venous blood was sent for haematocrit measurement between 2 and 6 hours of life. Repeat PCV is sent to babies with a prior value of PCV >65% at 36 hours of life or before discharge. PSV, end diastolic velocity (EDV), RI of ACA and MCA were measured using Mindray portable ultrasound machine with a mini- curved ultrasound transducer (8-13 mhz). Data is entered in excel and analysed. Results: Out of 75 enrolled babies, 19 had polycythaemia. The mean PSV±SD of MCA was 27.84±6.04 cm/s and 27.27±5.74 cm/s in the normocythemia and polycythemia groups, respectively, at 6 hours of life, which is statistically insignificant. The mean PSV±SD of MCA was 31.41±6.92 cm/s and 29.61±6.57 cm/s in normocythemia and polycythaemia groups, respectively, at 36 hours of life, which is statistically insignificant too. Conclusions: Cerebral Doppler values did not correlate with haematocrit between the normocythemia and polycythemia groups in the neonates at risk of polycythemia.